Indigenous knowledge systems and climate change management in Africa - Mafongoya, P.L.; Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2017)
Climate change presents a profound challenge to food security and sustainable development in Africa. Its negative impacts are likely to be greatest in the African region, which is already food insecure. In the face of global climate change and its emerging challenges and unknowns, it is essential that decision makers base policies on the best available knowledge. In recent years, the knowledge of local and indigenous people, often referred to as indigenous knowledge (IK) has been increasingly recognised as an important source of climate knowledge and adaptation strategies.